2015 12th International Conference on Fuzzy Systems and Knowledge Discovery (FSKD) 2015
DOI: 10.1109/fskd.2015.7382376
|View full text |Cite
|
Sign up to set email alerts
|

MatchingSem: Online recruitment system based on multiple semantic resources

Abstract: The growth of online recruitment has spurred the need for more effective automated systems. On the one hand, traditional approaches based on keyword-based matching techniques suffer from low precision, i.e. a large fraction of the systems' suggestions are irrelevant. On the other hand, the newer semantics-based approaches are penalized by limitations of the exploited semantic resources, namely semantic knowledge incompleteness and limited domain coverage. In this paper, we present an automatic semantics-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…For instance, in Wimalasuriya and Dou (2009), the authors demonstrated through experimental results that by using multiple ontologies the quality of the system's precision can be improved. Similarly, Kmail et al (2015) have confirmed the increase in the system's effectiveness when utilising multiple semantic resources for the purposes of matching resumes to their corresponding job posts. However, the authors in this work have also acknowledged the fact that even with the exploitation of multiple semantic resources, some entities were still unrecognised by any of the used resources.…”
Section: Related Workmentioning
confidence: 56%
See 3 more Smart Citations
“…For instance, in Wimalasuriya and Dou (2009), the authors demonstrated through experimental results that by using multiple ontologies the quality of the system's precision can be improved. Similarly, Kmail et al (2015) have confirmed the increase in the system's effectiveness when utilising multiple semantic resources for the purposes of matching resumes to their corresponding job posts. However, the authors in this work have also acknowledged the fact that even with the exploitation of multiple semantic resources, some entities were still unrecognised by any of the used resources.…”
Section: Related Workmentioning
confidence: 56%
“…With the growing interest in semantic resources, several recent approaches have been proposed for semantically analysing user queries and matching them at a semantics-based level to their related documents. However, these approaches either use a single semantic resource such as Lu et al (2015), , Han et al (2016), Selmi et al (2018), Boiński et al (2018) and Royo et al (2005) or multiple heterogeneous semantic resources such as Maree et al (2016), Vigneshwari and Aramudhan (2015), Shen and Lee (2018), Kmail et al (2015), Zhu and Iglesias (2018), Goldfarb and Le Franc (2017) and Wimalasuriya and Dou (2009). For instance, the system proposed in Royo et al (2005) maps query keywords to their corresponding synsets in WordNet ontology.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Третий подход -использование семантики [17,18] для решения задачи классификации резюме. Исследование [6] выявляет повторяющиеся особенности в семействах должностей при помощи метода LDA [13,14] и кластеризации (K-means) [21,23] и использует их для характеристики каждой области. В нем также рассматривается относительная важность различных наборов навыков в этих группах должностей.…”
Section: материалы и методыunclassified